Catalyst. - Giblin, Tessa; Serino, Angela; Michiels, Stani; Van de Vijver, Gertrudis; Spreeuwenberg, Jaap; Vanhee, Sarah; van Campenhout, Elke; van der Duin, Patrick; van Houten, Ledjaar; Pasi, Marco; Vlaams Cultuurhuis de Brakke Grond, Amsterdam (Amsterdam : Vlaams cultuurhuis de Brakke Grond, 2006)
Desmet, Thomas ; Leplae, Marlies ; Detige, Ronald ; Arens, Johann ; al Solh, Mourina ; de Roeck, Filip ; Kanazawa, Reiko ; Klijn, Sandor
Catalyst is a series of conversations, an exhibition and a catalogue as well as a residency, artist-run space forum and other events ; openend July 21, 2006, Vlaams cultuurhuis de Brakke Grond
kunstcatalogus